Association between mobility spinal cord independence measure (MSCIM) and period of walking recovery in spinal tuberculosis - L.N. Yong; Fatimah Ahmedy; Khin Nyein Yin; S.S. Syah; Tan Soo Fun; N.M. Tuah (Faculty of Science and Natural Resources, 2020)
This study aimed to identify the association between initial Spinal Cord Independence Measure’s Mobility Sub-score (mSCIM) and the period of walking recovery in Spinal Tuberculosis (STB). This retrospective cohort study divided 36 STB patients into two groups by their initial mSCIM score: ‘mSCIM<13’ and ‘mSCIM≥13’. Both groups were retrospectively followed-up from diagnosis until one year via clinical records. Baseline characteristics, walking outcome and period of walking recovery were recorded. Logical regression tested the association between mSCIM and walking outcome while a timeto-event analysis was done to test the relationship between mSCIM and period of walking recovery. Both ‘mSCIM<13’ and ‘mSCIM≥13’ groups had 18 patients each. Logical regression showed the mSCIM≥13 group had higher probability of recovering their walking ability (p=0.021). Time-to-event analysis showed both groups had significantly different period of walking recovery (p=0.001), averaging 10.44 and 4.94 months in those with mSCIM<13 and mSCIM≥13 respectively. In conclusion, patients with mSCIM≥13 require significantly shorter period of walking recovery.